A process for removing calcium from lithium liquid and its application
By adding sodium oxalate and sodium hydroxide to the lithium liquid, and using the filtration step of a macroporous resin column and a modified ceramic membrane, the calcium and magnesium impurities in the lithium liquid were successfully removed, solving the problem of these impurities affecting the purity of lithium phosphate, and improving the safety and stability of the battery.
Patent Information
- Application Number
- CN202410971192.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-07-19
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2044-07-19
AI Technical Summary
The salt lake lithium extraction tail liquid contains impurities such as calcium and magnesium, which affects the purity of lithium phosphate and the safety and stability of the battery. It is difficult for the prior art to remove these impurities efficiently.
The method of adjusting pH value of sodium oxalate and sodium hydroxide is used to combine the filtration step of macroporous resin column and modified ceramic membrane to remove calcium and magnesium ions in the lithium liquid to reduce the loss of lithium.
Significantly reduce the concentration of calcium ions and magnesium ions in lithium liquid, reduce the lithium loss rate, improve the purity of lithium phosphate products, and enhance the safety and stability of the battery.
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of batteries, and in particular relates to a process method and application of removing calcium from lithium liquid. Background Art
[0002] Since the 21st century, the new energy industry has developed rapidly, and the price of lithium carbonate used to synthesize lithium iron phosphate has skyrocketed. However, people have found that lithium phosphate can also be used as a lithium source for the preparation of lithium iron phosphate, but the purity of lithium phosphate is required to be higher than 99.5%.
[0003] Most of my country's lithium resources come from salt lakes, but when lithium is extracted from salt lakes, some lithium is still in the tail liquid. Direct discharge not only pollutes the environment, but also causes waste of lithium resources. Therefore, its recycling is of great significance for sustainable development. Tail liquid is generally used to prepare lithium phosphate, but lithium phosphate recovered from tail liquid contains a variety of impurities such as sodium, potassium, boron, chlorine, calcium, and magnesium. Among them, impurities such as calcium and magnesium are similar in nature to lithium and are difficult to remove, affecting the purity of lithium phosphate, and further affecting the safety and stability of batteries prepared from lithium phosphate.
[0004] Therefore, removing calcium and magnesium from lithium liquid is of great significance for improving the comprehensive utilization rate of salt lakes and lithium phosphate. Summary of the invention
[0005] The purpose of the present invention is to provide a process method and application for removing calcium from lithium liquid. The process method of the present invention processes lithium liquid, which can significantly reduce the concentration of calcium ions and magnesium ions in the lithium liquid, while reducing the lithium loss rate and improving the purity of the final lithium phosphate product.
[0006] In order to achieve the above object, the present invention provides the following technical solutions:
[0007] The process for removing calcium from the lithium solution comprises the following steps:
[0008] S1. Add sodium oxalate to the lithium solution, and add sodium hydroxide to adjust the pH value of the solution to 6-7, react at room temperature at a stirring rate of 200-400 r / min for 1-2 hours, and filter to obtain solution 1;
[0009] S2, passing solution 1 through a macroporous resin column at a flow rate of 10 to 15 BV / h to obtain solution 2;
[0010] S3, filtering the solution 2 with a modified ceramic membrane to obtain a solution 3;
[0011] S4, precipitating lithium in the solution and purifying it to obtain a lithium phosphate product.
[0012] Preferably, the lithium liquid is the tail liquid after lithium extraction from a salt lake.
[0013] Preferably, the lithium content in the lithium solution is 15% to 20%, the concentration of calcium ions is 10 to 40 mg / L, and the concentration of magnesium ions is 1 to 10 mg / L.
[0014] In some preferred embodiments, the lithium liquid comes from Guangdong Weimar New Materials Co., Ltd.
[0015] Preferably, the solid-liquid ratio of the sodium oxalate and lithium liquid is (3-5) g:1L.
[0016] The inventors found that by adding an appropriate amount of sodium oxalate and controlling the reaction conditions at the same time, a large amount of calcium ions and magnesium ions in the lithium solution can be removed, while reducing the loss of lithium. This may be because sodium oxalate can react with calcium ions and magnesium ions in the lithium solution to generate calcium oxalate and magnesium oxalate precipitates, respectively, and then remove them by filtration, and the introduction of sodium oxalate will not add additional impurities. However, it is necessary to control the amount of sodium oxalate added and the reaction conditions during the experiment. Excessive addition of sodium oxalate will not only cause the oxalate ions in the system to hydrolyze and generate hydroxide radicals, but also convert the hydrogen phosphate ions in the solution into phosphate ions, increasing the loss of lithium, and the sodium ion concentration increases the solubility of calcium oxalate in the system, affecting the removal rate of calcium ions and magnesium ions. And too high agitation rate will also destroy calcium oxalate and magnesium oxalate precipitates, affecting their removal rate. However, only sodium oxalate is limited to the removal of calcium ions and magnesium ions through chemical precipitation, and forcing the removal rate to increase will increase the loss of lithium.
[0017] Preferably, the macroporous resin column is filled with macroporous resin.
[0018] Preferably, the macroporous resin has aminophosphoric acid groups.
[0019] Preferably, the macroporous resin has a mass exchange capacity (chelated calcium) of ≥1.45 mmol / g, a volume exchange capacity (chelated calcium) of ≥0.5 mmol / g, and an effective particle size of 0.4 to 0.7 mm.
[0020] In some preferred embodiments, the macroporous resin is purchased from D402 chelating resin produced by Secos Resins Co., Ltd.
[0021] The inventors found that the macroporous resin column loaded with a specific macroporous resin was selected to process the solution, which can further remove the calcium ions and magnesium ions in the lithium solution without affecting the lithium ion concentration and causing no loss to the lithium. This may be because the aminophosphoric acid group on the macroporous resin can form a stable coordination bond with the metal ion, especially for calcium ions and magnesium ions, the coordination bond formed is more stable than the lithium ion, so in the adsorption process, calcium ions and magnesium ions are more easily adsorbed by the resin, and lithium ions are retained in the solution due to their low affinity with the resin. In addition, the resin has a porous structure, and these pores provide abundant adsorption sites for calcium ions and magnesium ions. However, it is necessary to control the liquid flow rate during the adsorption process, and too fast a flow rate may lead to incomplete adsorption, and too fast a flow rate may cause the resin adsorption capacity saturation time to be too long, and low-affinity lithium ions may also be adsorbed.
[0022] Preferably, the transmembrane pressure difference during the filtration in step S3 is 0.05 to 0.15 MPa.
[0023] The method for preparing the modified ceramic membrane comprises the following steps:
[0024] B1. Take a silane coupling agent and hydrolyze it in an ethanol aqueous solution with a concentration of 80wt% and heat it to 55-65°C. After immersing the ceramic membrane in the solution for 2-4 hours, rinse it with deionized water and dry it at 100-120°C for 3-5 hours to obtain a silane coupling agent modified ceramic membrane;
[0025] B2. Prepare polyvinyl alcohol into a polyvinyl alcohol aqueous solution with a mass concentration of 0.5% to 2%, add graphene oxide thereto and disperse evenly to obtain a mixed solution, use a vacuum migration method to completely immerse the silane coupling agent modified ceramic membrane in the mixed solution, vacuum treat for 20 to 30 minutes, then take it out, and heat treat it at 100 to 200° C. for 1 to 3 hours to obtain the obtained product.
[0026] In some preferred schemes, the solution is filtered by a modified ceramic membrane, and calcium ions, magnesium ions, etc. larger than the membrane pore size can be retained on one side of the membrane, thereby achieving the removal of calcium ions and magnesium ions. However, the removal capacity will be weakened over a long period of time, and the removal of other impurities in the solution is limited, and the improvement of the purity of lithium phosphate is limited. The inventors found that constructing a layer of new graphene oxide film on the surface of the ceramic membrane can improve the stability of the modified ceramic membrane while also increasing the adsorption of other impurities in the lithium solution, thereby improving the purity of the prepared lithium phosphate. This may be because graphene oxide has a large specific surface area and abundant adsorption sites, and contains active functional groups such as hydroxyl and carboxyl groups, so it can effectively adsorb heavy metal ions, organic pollutants, etc. in water. In addition, the layered structure of graphene oxide also provides it with more adsorption space, making its adsorption capacity relatively large. Thereby greatly improving the purity of the lithium phosphate finally obtained, while improving the removal rate of calcium ions and magnesium ions. However, the adhesion effect between graphene oxide and ceramic membrane is poor.
[0027] Preferably, the volume ratio of the silane coupling agent to the ethanol aqueous solution is 1:30-50; more preferably, it is 1:40.
[0028] Preferably, the silane coupling agent is one or more of KH550, KH560, KH570, KH590, and KH792; more preferably, it is KH550 and KH590.
[0029] Preferably, the mass ratio of KH550 to KH590 is 1:(5-7); more preferably, it is 1:6.
[0030] Preferably, the ceramic membrane has a pore size of 100 to 200 nm, is made of Al2O3-ZrO2, and is purchased from the Institute of Membrane Science and Technology of Nanjing University of Technology.
[0031] The inventors found through a large number of experiments that by selecting two silane coupling agents to modify the ceramic membrane, amino groups, thiol groups and other functional groups are grafted on the surface of the ceramic membrane, which can react with the epoxy groups on the graphene oxide, so that the graphene oxide can adhere to the ceramic membrane, thereby improving the adsorption effect of the ceramic membrane; at the same time, by controlling the particle size and other properties of the ceramic membrane and graphene oxide, the prepared modified ceramic membrane can accurately filter precipitates such as calcium oxalate and magnesium oxalate that are difficult to filter by ordinary filtering means, further improving the purity of the final lithium phosphate.
[0032] Preferably, the alcoholysis degree of the polyvinyl alcohol is ≥99%, the ash content is ≤0.5%, and the viscosity of the polyvinyl alcohol prepared into a 4 wt % aqueous solution is 15-25 CP.
[0033] In some preferred embodiments, the polyvinyl alcohol is purchased from Japan Kuraray polyvinyl alcohol 80-18.
[0034] Preferably, the graphene oxide includes single-layer graphene oxide and multi-layer graphene oxide.
[0035] Preferably, the weight ratio of the single-layer graphene oxide to the multi-layer graphene oxide is 1:(0.5-2); further preferably, it is 2:3.
[0036] Preferably, the average thickness of the single-layer graphene oxide is 0.5 to 1.2 nm, and the diameter is 4 to 7 μm.
[0037] Preferably, the multilayer graphene oxide has an average thickness of 1 to 3 nm, a diameter of 4 to 7 μm, and 2 to 5 layers.
[0038] In some preferred embodiments, the single-layer graphene oxide and the multi-layer graphene oxide are both purchased from Zhejiang Zhiti Nano Micro New Materials Co., Ltd.
[0039] Preferably, the solid-to-liquid ratio of the graphene oxide to the polyvinyl alcohol aqueous solution is 1-10 g:100 mL.
[0040] In order to improve the filtering effect and stability of the ceramic membrane, two specific graphene oxides are selected to modify it. This may be because on the one hand, specific single-layer graphene oxide and multi-layer graphene oxide are selected, which have similar diameters and little difference in thickness, so there is a certain compatibility between the two. On the one hand, the complementarity in the number of layers is achieved, which not only retains the high activity of the single-layer graphene oxide, but also improves the mechanical properties of the product. On the other hand, the single-layer and multi-layer graphene oxides of similar size are intertwined and stacked to form a stable three-dimensional network structure, which can improve the structural stability of the modified ceramic membrane. In addition, the additive liquid of specific polyvinyl alcohol can improve the adhesion of the ceramic membrane matrix and graphene oxide, thereby also improving the structural stability of the modified ceramic membrane. However, considering the agglomeration effect of graphene oxide, its addition amount should not be too much, and excessive agglomerated graphene oxide loaded on the surface of the ceramic membrane may block the ceramic pores and affect the filtering effect.
[0041] The specific steps of lithium precipitation are: concentrating the solution to a lithium ion concentration of 5 to 7 g / L, adding sodium phosphate to adjust the molar ratio of lithium to phosphorus in the solution to 3: (1 to 1.05), adjusting the temperature to 80 to 90° C., adding sodium hydroxide to adjust the pH of the solution to 9 to 10, and filtering after complete precipitation.
[0042] The specific steps of the purification are: adding 5 to 8 times the mass of distilled water to the product after lithium precipitation, heating to 80 to 90° C., stirring for 1 to 2 hours, filtering, and drying the product to obtain the lithium phosphate product.
[0043] The process for removing calcium from lithium liquid of the present invention is applied to the field of batteries.
[0044] Compared with the prior art, the advantages and beneficial effects of the present invention are:
[0045] 1. The present invention provides a process method and application for removing calcium from lithium liquid, which can significantly reduce the concentration of calcium ions and magnesium ions in the lithium liquid, while reducing the lithium loss rate and improving the purity of the final lithium phosphate product. In addition, the tail liquid of lithium extraction from salt lakes can also be recovered, which is of great significance to the sustainable development strategy.
[0046] 2. The present invention adds an appropriate amount of sodium oxalate and controls the reaction conditions, thereby being able to remove a large amount of calcium ions and magnesium ions in the lithium solution and reducing the loss of lithium.
[0047] 3. The present invention uses a macroporous resin column loaded with a specific macroporous resin to treat solution 1, which can further remove calcium ions and magnesium ions in the lithium solution without affecting the lithium ion concentration.
[0048] 4. The present invention constructs a new graphene oxide film on the surface of the ceramic membrane, which can improve the stability of the modified ceramic membrane and also increase the adsorption of other impurities in the lithium liquid, thereby improving the purity of the prepared lithium phosphate.
[0049] 5. The present invention uses two silane coupling agents to modify the ceramic membrane, thereby improving the adhesion between graphene oxide and the ceramic membrane, improving the adsorption effect of the modified ceramic membrane, and at the same time improving the purity of the final lithium phosphate.
[0050] 6. The present invention selects two specific graphene oxides for modification and adds specific polyvinyl alcohol, which can improve the filtering effect and stability of the modified ceramic membrane. DETAILED DESCRIPTION
[0051] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0052] The raw materials used in the present invention are all commercially available, specifically:
[0053] The lithium content in the lithium liquid is 18.2%, the concentration of calcium ions is 28.8 mg / L, and the concentration of magnesium ions is 6.7 mg / L. It comes from Guangdong Weimar New Materials Co., Ltd.
[0054] The macroporous resin has aminophosphoric acid groups, a mass exchange capacity (chelated calcium) ≥ 1.45 mmol / g, a volume exchange capacity (chelated calcium) ≥ 0.5 mmol / g, an effective particle size of 0.4-0.7 mm, and is purchased from D402 chelating resin produced by Secos Resin Co., Ltd.
[0055] The ceramic membrane has a pore size of 150 nm and is made of Al2O3-ZrO2, which was purchased from the Institute of Membrane Science and Technology of Nanjing University of Technology.
[0056] Polyvinyl alcohol, with alcoholysis degree ≥ 99% and ash content ≤ 0.5%, is prepared into a 4 wt % aqueous solution with a viscosity of 15-25 CP and is purchased from Kuraray Polyvinyl Alcohol 80-18 from Japan.
[0057] The average thickness of the single-layer graphene oxide is 0.5-1.2 nm, and the diameter is 4-7 μm; the average thickness of the multi-layer graphene oxide is 1-3 nm, the diameter is 4-7 μm, and the number of layers is 2-5; both are purchased from Zhejiang Zhiti Nano Micro New Materials Co., Ltd.
[0058] Example 1
[0059] This embodiment provides a process for removing calcium from lithium liquid, the steps are:
[0060] S1, adding sodium oxalate to the lithium solution, and adding sodium hydroxide to adjust the pH value of the solution to 6.5, reacting at room temperature at a stirring rate of 300 r / min for 1.5 h, and filtering to obtain solution 1;
[0061] S2, passing solution 1 through a macroporous resin column at a flow rate of 12 BV / h to obtain solution 2;
[0062] S3, filtering the solution 2 with a modified ceramic membrane to obtain a solution 3;
[0063] S4, precipitating lithium in the solution and purifying it to obtain a lithium phosphate product.
[0064] The solid-to-liquid ratio of the sodium oxalate and lithium liquid is 4g:1L.
[0065] The transmembrane pressure difference during the filtration in step S3 is 0.1 MPa.
[0066] The method for preparing the modified ceramic membrane comprises the following steps:
[0067] B1. The silane coupling agent is hydrolyzed in an ethanol aqueous solution with a concentration of 80 wt % and heated to 60° C. The ceramic membrane is immersed in the solution for 3 hours, then rinsed with deionized water and dried at 110° C. for 4 hours to obtain a silane coupling agent modified ceramic membrane;
[0068] B2. Prepare polyvinyl alcohol into a polyvinyl alcohol aqueous solution with a mass concentration of 1%, add graphene oxide thereto and disperse evenly to obtain a mixed solution, use a vacuum migration method to completely immerse the silane coupling agent modified ceramic membrane in the mixed solution, vacuum treat for 25 minutes, then take it out, and heat treat it at 150°C for 2 hours to obtain the product.
[0069] The volume ratio of the silane coupling agent to the ethanol aqueous solution is 1:40.
[0070] The silane coupling agents are KH550 and KH590.
[0071] The mass ratio of KH550 to KH590 is 1:6.
[0072] The graphene oxide is single-layer graphene oxide and multi-layer graphene oxide.
[0073] The weight ratio of the single-layer graphene oxide to the multi-layer graphene oxide is 2:3.
[0074] The solid-to-liquid ratio of the graphene oxide to the polyvinyl alcohol aqueous solution is 5 g:100 mL.
[0075] The specific steps of lithium precipitation are: concentrating the solution to a lithium ion concentration of 6 g / L, adding sodium phosphate to adjust the molar ratio of lithium and phosphorus in the solution to 3:1.02, adjusting the temperature to 85°C, adding sodium hydroxide to adjust the pH of the solution to 9.5, and filtering after complete precipitation.
[0076] The specific steps of the purification are: adding 7 times the mass of distilled water to the product after lithium precipitation, heating to 85° C., stirring for 1.5 hours, filtering, and drying the product to obtain the lithium phosphate product.
[0077] Example 2
[0078] The difference between this embodiment and embodiment 1 is: S1, sodium oxalate is added to the lithium solution, and sodium hydroxide is added to adjust the pH value of the solution to 6, and the mixture is reacted at a stirring rate of 400 r / min at room temperature for 1.5 h, and filtered to obtain solution 1; the solid-liquid ratio of the sodium oxalate to the lithium solution is 5 g:1 L.
[0079] Example 3
[0080] The difference between this embodiment and embodiment 1 is that the weight ratio of the single-layer graphene oxide to the multi-layer graphene oxide is 1:1.
[0081] Comparative Example 1
[0082] The difference between this comparative example and Example 1 is that the solid-to-liquid ratio of the sodium oxalate and the lithium liquid is 8g:1L.
[0083] Comparative Example 2
[0084] The difference between this comparative example and Example 1 is as follows: S1, sodium oxalate is added to the lithium solution, and sodium hydroxide is added to adjust the pH value of the solution to 6.5, and the mixture is reacted at room temperature at a stirring rate of 500 r / min for 1.5 h, and filtered to obtain Solution 1.
[0085] Comparative Example 3
[0086] The difference between this comparative example and Example 1 is that there are carboxylic acid groups on the macroporous resin, the mass total exchange capacity is ≥10.8mmol / g, the volume total exchange capacity is ≥4.2mmo l / g, the effective particle size is 0.4-0.7mm, and it is purchased from D113 resin produced by Bengbu Sany Resin Technology Co., Ltd.
[0087] Comparative Example 4
[0088] The difference between this comparative example and Example 1 is that the pore size of the ceramic membrane is 400 nm, and the material is Al2O3-ZrO2, which is purchased from the Institute of Membrane Science and Technology of Nanjing University of Technology.
[0089] Comparative Example 5
[0090] The difference between this comparative example and Example 1 is that the alcoholysis degree of polyvinyl alcohol is 86% to 90%, the ash content is ≤0.7%, the viscosity is 4.5 to 6.5 mPa·s, and it is purchased from Shanxi Sanwei Shengtai New Material Technology Co., Ltd. 88-05.
[0091] Comparative Example 6
[0092] The difference between this comparative example and Example 1 is that the silane coupling agent is KH550.
[0093] Comparative Example 7
[0094] The difference between this comparative example and Example 1 is that the graphene oxide is a single-layer graphene oxide.
[0095] Performance Testing
[0096] The calculation formula for calcium and magnesium removal rate is: (1-(volume of solution three × calcium / magnesium concentration in solution three) / (volume of lithium solution × calcium / magnesium concentration in lithium solution)) × 100%. The calculation formula for lithium loss rate is: (1-(volume of solution three × lithium concentration in solution three) / (volume of lithium solution × lithium concentration in lithium solution)) × 100%. The calculation formula for the purity of lithium phosphate products is: 5.56 × the proportion of lithium elements in lithium phosphate products × 100%. The results are shown in Table 1.
[0097] Table 1 Measurement results
[0098] Calcium removal rate / % Magnesium removal rate / % Lithium loss rate / % Lithium phosphate purity / % Example 1 99.3 90.5 4.2 99.8 Example 2 98.9 89.1 4.0 99.6 Example 3 99.1 90.1 4.2 99.7 Comparative Example 1 95.4 84.5 5.9 98.2 Comparative Example 2 96.2 85.1 5.5 98.4 Comparative Example 3 90.3 79.4 6.3 95.7 Comparative Example 4 94.2 83.5 6.1 96.5 Comparative Example 5 97.3 86.9 5.7 97.6 Comparative Example 6 96.6 86.5 6.0 97.3 Comparative Example 7 95.7 84.9 6.3 95.2
[0099] According to statistics, the lithium phosphate products prepared by Examples 1 to 3 of the present invention are all relatively high, with high efficiency in removing calcium and magnesium, while reducing the loss of lithium. The amount of oxalic acid added in Comparative Example 1 is too high, the stirring rate in Comparative Example 2 is too fast, Comparative Example 3 does not use a specific macroporous resin, the membrane pore size in Comparative Example 4 is too large, affecting the filtering effect, Comparative Example 5 does not use a specific polyvinyl alcohol, Comparative Example 6 does not add silane coupling agent KH590, and Comparative Example 7 does not add multilayer graphene oxide. The purity of the prepared phosphoric acid products is relatively low, the removal rates of calcium and magnesium are relatively low, and the lithium loss rate is relatively high. Therefore, the method described in this application is used to remove calcium from the lithium solution, which can not only significantly reduce the concentration of calcium ions and magnesium ions in the lithium solution, but also reduce the lithium loss rate and improve the purity of the lithium phosphate product finally obtained.
[0100] The above is a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principles of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A process for removing calcium from lithium liquid, characterized in that: The steps are: S1. Add sodium oxalate to the lithium solution, and add sodium hydroxide to adjust the pH value of the solution to 6-7, react at room temperature at a stirring rate of 200-400 r / min for 1-2 hours, and filter to obtain solution 1; S2, passing solution 1 through a macroporous resin column at a flow rate of 10 to 15 BV / h to obtain solution 2; S3, filtering the solution 2 with a modified ceramic membrane to obtain a solution 3; S4, precipitating lithium in the solution and purifying it to obtain a lithium phosphate product; The macroporous resin column is filled with macroporous resin; the macroporous resin has aminophosphoric acid groups; the mass exchange capacity of the macroporous resin is ≥1.45mmo l / g in terms of chelated calcium, the volume exchange capacity is ≥0.5mmo l / g in terms of chelated calcium, and the effective particle size is 0.4-0.7mm; The method for preparing the modified ceramic membrane comprises the following steps: B1. Take a silane coupling agent and hydrolyze it in an ethanol aqueous solution with a concentration of 80wt% and heat it to 55-65°C. After immersing the ceramic membrane in the solution for 2-4 hours, rinse it with deionized water and dry it at 100-120°C for 3-5 hours to obtain a silane coupling agent modified ceramic membrane; B2, polyvinyl alcohol is prepared into a polyvinyl alcohol aqueous solution with a mass concentration of 0.5% to 2%, graphene oxide is added thereto and dispersed evenly to obtain a mixed solution, and the silane coupling agent modified ceramic membrane is completely immersed in the mixed solution by a vacuum migration method, and the silane coupling agent is vacuum treated for 20 to 30 minutes, then taken out, and heat treated at 100 to 200° C. for 1 to 3 hours to obtain; The silane coupling agents are KH550 and KH590; The graphene oxide includes single-layer graphene oxide and multi-layer graphene oxide.
2. The process for removing calcium from lithium liquid according to claim 1, characterized in that: The lithium liquid is the tail liquid after lithium is extracted from the salt lake.
3. The process for removing calcium from lithium liquid according to claim 1, characterized in that: The lithium content of the lithium solution is 15% to 20%, the concentration of calcium ions is 10 to 40 mg / L, and the concentration of magnesium ions is 1 to 10 mg / L.
4. The process for removing calcium from lithium liquid according to claim 1, characterized in that: The solid-to-liquid ratio of the sodium oxalate and lithium liquid is (3-5) g:1L.
5. The process for removing calcium from lithium liquid according to claim 1, characterized in that: The pore size of the ceramic membrane is 100-200 nm, and the material is Al2O3-ZrO2.
6. The process for removing calcium from lithium liquid according to claim 1, characterized in that: The alcoholysis degree of the polyvinyl alcohol is ≥99%, the ash content is ≤0.5%, and the viscosity of the polyvinyl alcohol prepared into a 4wt% aqueous solution is 15-25CP.
7. The process for removing calcium from lithium liquid according to claim 1, characterized in that: The average thickness of the single-layer graphene oxide is 0.5-1.2 nm, and the diameter is 4-7 μm; the average thickness of the multi-layer graphene oxide is 1-3 nm, and the diameter is 4-7 μm, and the number of layers is 2-5.
8. An application of the process for removing calcium from lithium liquid according to any one of claims 1 to 7, characterized in that: Used in the battery field.
Citation Information
Patent Citations
Purification method of crude lithium phosphate
CN115583638A